Determination of trace compounds and artifacts in nitrogen background measurements by proton transfer reaction time‐of‐flight mass spectrometry under dry and humid conditions. (22nd July 2021) - Salazar Gómez, Jorge Iván; Sojka, Martha; Klucken, Christian; Schlögl, Robert; Ruland, Holger
Abstract: A qualitative analysis was applied for the determination of trace compounds at the parts per trillion in volume (pptv ) level in the mass spectra of nitrogen of different qualities (5.0 and 6.0) under dry and humid conditions. This qualitative analysis enabled the classification and discovery of hundreds of new ions (e.g., [S x ]H + species) and artifacts such as parasitic ions and memory effects and their differentiation from real gas impurities. With this analysis, the humidity dependency of all kind of ions in the mass spectrum was determined. Apart from the inorganic artifacts previously discovered, many new organic ions were assigned as instrumental artifacts and new isobaric interferences could be elucidated. From 1140 peaks found in the mass range m/z 0–800, only 660 could be analyzed due to sufficient intensity, from which 463 corresponded to compounds. The number of peaks in nitrogen proton transfer reaction (PTR) spectra was similarly dominated by nonmetallic oxygenated organic compounds (23.5%) and hydrocarbons (24.1%) Regarding only gas impurities, hydrocarbons were the main compound class (50.2%). The highest contribution to the total ion signal for unfiltered nitrogen under dry and humid conditions was from nonmetallic oxygenated compounds. Under dry conditions, nitrogen‐containing compounds exhibit the second highest contribution of 89% and 96% for nitrogen 5.0 and 6.0, respectively, whereas under humid conditions, hydrocarbons become the second dominant group with 69% and 86% for nitrogen 5.0 and 6.0, respectively. With the gathered information, a database can be built as a tool for the elucidation of instrumental and intrinsic gas matrix artifacts in PTR mass spectra and, especially in cases, where dilution with inert gases plays a significant role.